PROTOTYPE DEVELOPMENT OF LABVIEW BASED DATA PROCESSING OF TRAIN DYNAMIC RESPONSE AND LOCATION - Arkan, Ghazy
Railway track serves as a medium in which train is operated. Due to constant exposure to various load and weather, the railway track can be damaged. The damage in railway track can affect safety and comfortability in train operation. To identify railway track damage, a monitoring process needs to be conducted. In Indonesia, a monitoring process is still done by operating the track-recording vehicle. But that method is costly to operate, and it can disturb the passengers’ train route. To solve that problem, this research is conducted to develop a measurement system based on dynamic response of in-service train. The dynamic response is measured by placing a measurement device inside the train cabin. This research is developing a monitoring system by using accelerometer as vibration measuring tool, IMU (Inertial Measurement Unit) sensor as train angular position measuring tool, and GPS (Global Position System) receiver as location determining tool. That monitoring system using LabVIEW based Virtual Instrument as its display. The monitoring system that has been developed will be tested for performance which include laboratory and field test. The Laboratory test is conducted to examine the performance and determine the error value in IMU sensor and GPS receiver. The field test is conducted to examine the performance of the monitoring system in anomaly detection and their corresponding location along the test track. The results of the conducted laboratory testing shows that IMU sensor has an average measurement error value of 1.24% on the x-axis (roll), 1,62% on the y-axis (pitch), and 2,82% on the z-axis (yaw). GPS receiver has an average measurement error value of 14.89%. During the field testing, it can be seen that the monitoring system is capable of detecting anomalies and its coordinate location along the test track.